Strategi Pencitraan Pariwisata Sri Lanka Melalui Eco-Cultural Tourism Pasca Konflik Etnis Tahun 2011-2016 - Rismaya Dewi, Ni Made Ari; Priadarsini, Ni Wayan Rainy; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This study aims to analyze Sri Lanka's imaging strategy through eco-cultural tourism after the 2011-2016 ethnic conflict using qualitative research methods. Sri Lanka has the potential for nature and culture-based tourism or currently known as eco-cultural tourism. However, tourism in Sri Lanka had experienced a drastic decline due to ethnic conflicts that occurred for 26 years. With the desire to develop its tourism, Sri Lanka is re-implementing a tourism strategy as well as to build its image even though it has just been separated from ethnic conflicts through the "Sri Lanka Tourism Development Strategy 2011-2016" internally and especially externally. Researcher uses the framework of national image and cultural diplomacy to analyze Sri Lanka's imaging strategy. This research perceives that Sri Lanka's imaging strategy through cultural diplomacy is characterized by participation in international expos to international cooperation cultural diplomacy was marked by participating in international expos and participating in international forums.             Keyword: Sri Lanka, Eco-Cultural Tourism, Tourism Strategy, National Image, Cultural Diplomacy